Deformational Temperatures Across the Lesser Himalayan Sequence in Eastern Bhutan and Their Implications for the Deformation History of the Main Central Thrust. Issue 4 (25th March 2020) - Grujic, Djordje; Ashley, Kyle T.; Coble, Matthew A.; Coutand, Isabelle; Kellett, Dawn A.; Larson, Kyle P.; Whipp, David M.; Gao, Min; Whynot, Nicholas
Abstract: We postulate that the inverted metamorphic sequence in the Lesser Himalayan Sequence of the Himalayan orogen is a finite product of its deformation and temperature history. To explain the formation of this inverted metamorphic sequence across the Lesser Himalayan Sequence with a focus on the Main Central Thrust (MCT) in eastern Bhutan, we determined the metamorphic peak temperatures by Raman spectroscopy of carbonaceous material and established the deformation temperatures by Ti‐in‐quartz thermobarometry and quartz c axis textures. These data were combined with thermochronology, including new and published 40 Ar/ 39 Ar ages of muscovite and published apatite fission track, and apatite and zircon (U‐Th)/He ages. To obtain accurate metamorphic, deformation, and closure temperatures of thermochronological systems, pressures and cooling rates for the period of interest were derived by inverse modeling of multiple thermochronological data sets, and temperatures were determined by iterative calculations. The Raman spectroscopy of carbonaceous material results indicate two temperature sequences separated by a thrust. In the external sequence, peak temperatures are constant across the structural strike, consistent with the observed hinterland‐dipping duplex system. In the internal temperature sequence associated with the MCT shear zone, each geothermometer yields an apparent inverted temperature gradient although with different temperature ranges, and all temperatures appear to be retrograde. These observations are consistent with the quartz microfabrics. Further, all thermochronometers indicate upward younging across the MCT. We interpret our data as a composite peak and deformation temperature sequence that formed successively and reflects the broadening and narrowing of the MCT shear zone in which the ductile deformation lasted until 11 Ma. Key Points: Crustal‐scale shear zones produce inverted temperature fields with transient gradients Each thermochronologic and thermobarometric method registers a different stage of such a temperature field Numerical modeling of multiple thermochronological data sets permits more detailed and accurate reconstruction of the thermal history of crustal‐scale shear zones